2007
DOI: 10.1029/2007gl030780
|View full text |Cite
|
Sign up to set email alerts
|

Recent volume loss of British Columbian glaciers, Canada

Abstract: [1] We use the Shuttle Radar Topography Mission (SRTM) data and digital terrain models from aerial photography to quantify the change of glacier volume in British Columbia (BC), Canada for the period 1985 -1999 ) is approximately double that observed for the previous two decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 13 publications
3
117
0
Order By: Relevance
“…We use the SRTM3, V2 without void filling (NASA et al, 2002). Many glacier elevation change studies have used this as a base dataset to compare to both newer and older data products (Rignot et al, 2003;Berthier et al, 2004;Larsen et al, 2007;Schiefer et al, 2007;Paul and Haeberli, 2008). Typically reported vertical uncertainties of the dataset are ≈ ±10 m which is lower than the mission standards of ±16 m (Rodriguez et al, 2006).…”
Section: Interferometric Srtm Demmentioning
confidence: 99%
“…We use the SRTM3, V2 without void filling (NASA et al, 2002). Many glacier elevation change studies have used this as a base dataset to compare to both newer and older data products (Rignot et al, 2003;Berthier et al, 2004;Larsen et al, 2007;Schiefer et al, 2007;Paul and Haeberli, 2008). Typically reported vertical uncertainties of the dataset are ≈ ±10 m which is lower than the mission standards of ±16 m (Rodriguez et al, 2006).…”
Section: Interferometric Srtm Demmentioning
confidence: 99%
“…This void-free SRTM version has been used in numerous glaciological studies, mainly related to the assessment of ice volume variations with time (e.g. Surazakov and Aizen, 2006;Berthier et al, 2007;Schiefer et al, 2007;Paul & Haeberli, 2008). The dataset is available in 5 by 5 degree tiles; tile 'srtm_52_06' covers the entire study region and was used here.…”
Section: Digital Elevation Modelsmentioning
confidence: 99%
“…Using SPOT and SRTM DEMs (Table 4), icefield geodetic balances were computed following the methods of Schiefer et al (2007) and Tennant et al (2012). For each icefield, SPOT and SRTM DEMs were reprojected to BC Albers and resampled to a 90 m resolution.…”
Section: Regional Glacier Mass Changementioning
confidence: 99%
“…In western North America, notable area and volume loss of glaciers (Larsen et al, 2007;Schiefer et al, 2007;Berthier et al, 2010;Bolch et al, 2010) and decreased late-summer flows in glacier-fed rivers (Stahl and Moore, 2006;Moore et al, 2009) have already been observed. On annual timescales, surface runoff in glacierized basins is affected by glacier mass change (Moore and Demuth, 2001) which supplements streamflow in years with thin snowpack or dry summers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation